Quality assurance of analytical results in environmental samples by means of participation in intercomparison round - Torres, Blanca (2003)
In developing countries, limited resources in the laboratories hinder quality assurance. One way to overcome this problem is to participate in international interlaboratory comparison rounds in order to asses the reliability and accuracy of the results, given by a particular laboratory. Considering that nuclear analytical techniques play an important role in the determination of minor and trace elements in biological and environmental samples, we report the performance of our neutron activation analysis and x ray fluorescence laboratories and how these laboratories have improved the quality of their results by participating in international analytical programmes for environmental samples such as: sediments, air filters, soil, water, algae, and herbs. The results of our participation in intercomparison round for quality assurance organized by AQCS-IAEA, and other institutes are presented, out of 103 reported results 91 were satisfactory.